Micropaleontological characteristics of the campanian-maastrichtian sediments in the Oskol river basin - МатвєєвA. В.; Шоміна, А. Д.; Колосова, І. В.; Синєгубка, В. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
Complexes of calcareous nannoplankton, foraminifera and ostracods in the Campanian and Maastrichtian sections were investigated in Kupyansk and Kamenka (Dvurechansky district). The rocks are presented by light gray chalk with a large admixture of clay. Ihnotextures are presented by a variety of the mud-eaters holes. The chalk is covered with Oligocene siltstone (Mezhigorskiy regional stage). The microfossils are diverse: 40 species of the calcareous nannoplankton, 39 - foraminifera and 13 – ostracods have been determined. The stratigraphic position of species has been traced. The most common nannofossils are large Broinsonia parca subsp. constricta Hattner et al., Broinsonia parca subsp. parca (Stradner), Arkhangelskiella cymbiformis Vekshina, Kamptnerius magnificus Deflandre, Micula staurophora Gardet. The complex of foraminifera mainly consists of species Gyroidina turgida (Hagenow), Parrella cordieriana (Orb.), Cibicides gancinoensis Nесkajа, Dentalina filiniformis (Orb.), Anomalina sp., Bifarina regularis Keller, that were found in large quantities in all samples. The majority of species refers to the benthic forms and only about 10% of the planktonic ones, namely Archaeoglobigerina blowi Pessagno, Archeoglobigerina cretacea (Orb.), Hedbergella delrioensis (Karsey), Gumbelina globulosa (Ehrenberg). The ostracods are mainly represented by Krithe simplex (Jones et Hinde), Krithe vanveenae Derro, Cytherella obovata Jones et Hinde species. UC15 and UC16 zones of the upper Campanian and UC17 of the lower Maastrichtian have been identified for calcareous nannoplankton. LC19 zone which belongs to the Upper Campanian has been identified for foraminifera. The layers with Krithe simplex have been identified for ostracods in the Upper Campanian. Changes in the complexes for certain groups of microfossils do not coincide. The nannofossils complex is found in the boreal region. The depth of sediment accumulation is defined by the ratio of planktonic and benthic foraminifera and ostracods complexes located at the depth 25-50 m.